2022
DOI: 10.1080/10872981.2022.2153396
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of the research on nursing students’ professional self-concept

Abstract: Objective To understand the current situation and progress of nursing students’ professional self-concept, this review aimed to perform a general analysis of research related to the connotation of professional self-concept, measurement tools, influencing factors, effects, and intervention experiments. Methods Three databases (Web of Science, PubMed, and CNKI) were searched for relevant articles. Research articles that met specific criteria were included, with identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Furthermore, in a study performed in Korea, Jeon and Koh (2017) found a positive effect of nurses' self-concept on their overall OCB. Recent research shows that nursesself-concept positively affects professional quality, academic performance and patient safety attitudes (Xu et al, 2023). In conclusion, these arguments suggest that nurses' self-concept mediates the relationship between POS and OCB directed toward different targets.…”
Section: H1 a Direct Positive Relationship Exists Between Pos And (A)...mentioning
confidence: 89%
See 3 more Smart Citations
“…Furthermore, in a study performed in Korea, Jeon and Koh (2017) found a positive effect of nurses' self-concept on their overall OCB. Recent research shows that nursesself-concept positively affects professional quality, academic performance and patient safety attitudes (Xu et al, 2023). In conclusion, these arguments suggest that nurses' self-concept mediates the relationship between POS and OCB directed toward different targets.…”
Section: H1 a Direct Positive Relationship Exists Between Pos And (A)...mentioning
confidence: 89%
“…This study used SET as a theoretical framework to explain how a positive initiating action, such as POS, can enhance positive employee responses, including greater commitment, OCB (Cropanzano et al, 2017) and a sense of competence in a specific domain (Eisenberger et al, 2020). Additionally, we used the expectancy-value model to explain how nurses' self-concept affects relational and behavioral social exchange outcomes (Cowin et al, 2008;Xu et al, 2023), such as OCB and affective commitment. Figure 1 illustrates the theoretical framework that underpins this study.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision regarding the choice of instrument was governed by the European origin thereof, since cross-border studies have demonstrated signi cant differences in the image of nurses coming from different cultures, and study methods often do not take into account cultural differences. 17,18 2. Materials and Methods…”
Section: Aimmentioning
confidence: 99%